COMPARATIVE EMIC-ETIC REVIEW OF ZHANG DE AND TROMPENAARS’S CORPORATE CULTURE - Assoc. Prof. Dr. Lee Kar Ling; Jing Chunqi (International Journal of Accounting, Finance and Business, 2021)
The paper focused on a literature review of organizational culture by analyzing the different dimensions between Western and Chinese organizational culture to ascertain whether there are similarities or differences using an emic-etic approach. The purpose of selecting a comparative review of Western and Chinese organization culture is due to the rise of China as an economic power house whereby more and more companies are beginning to query whether a Western or Chinese organization culture would better serve the organization given today’s global landscape. This study focuses on Trompenaars cultural dimensions as a representation of the Western organization culture as the cultural model is considered to be the most comprehensive as compared to other Western organization culture and China’s Zhangde’s dimensions of organizational culture since the latter’s organization cultural dimensions are distinctly Chinese in nature. Applied emic-etic research method combined with the specific cultural items of organizational culture between Western and China adopted as the research methodology. Such a methodology is qualitative in nature to determine whether a revised form of organizational culture model suitable for both the Western world and China’s company is possible for global companies investing in Asia and the Western world.